Common movement patterns of the jump shot while increasing the distance from the basket in elite basketball players - Podmenik, N.; Supej, M.; Debevec, H.; Erculj, F. (Journal of Human Kinetics, 2021)
he aim of this study was to examine chosen kinematic variables (duration of the shot, position of the centre of mass, position of the shooting hand, ro tation of the shoulder axis) of successful shots and to describe differences in movement patterns in elite basketball players while increasing the distance from the basket during a jump shot. Our participants were three elite shooting guards who were all Slovenian national team and Euroleague players. They were shooting from three differen t distances (3.75 m, 5.25 m, and 6.75 m); analysis includ ed 90 successful shots. The kinematics of the entire body was analysed using the inertial motion capture suit. The main interest was on the transverse plane (direction Y), focusing on rotational movements and movements to the left and right. The results showed that the rotation of the shoulder axis in the transverse plane, with all three participants, was greatest (p < .05) from the longest distance. Despite that graphs of individual players differed, deviation to the left was most significant while shooting from the largest distance for all participants. Also the landing from the jump shot was on the left according to the origin. For example, the average deviation to the left for player no. 2 was 11.9 ± 3.6 cm (the shortest distance), 12.6 ± 4.7 cm (the middle distance), and 23.3 ± 5.1 cm (the longest distance). Distance from the basket influenced the kinematics of the shot, especially from the longest distance. Along with the already well-known changes in the sagittal plane (direction X and Z), this research provides information on changes in the transverse plane, which are also very important, especially while shooting from longer distances.